2021
DOI: 10.3389/fcell.2021.655866
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Changes Associated With Sperm Fertilizing Ability in Meat-Type Roosters

Abstract: The molecular basis of male fertility remains unclear, especially in chickens, where decades of genetic selection increased male fertility variability as a side effect. As transcription and translation are highly limited in sperm, proteins are key molecules defining their functionality, making proteomic approaches one of the most adequate methods to investigate sperm capacity. In this context, it is interesting to combine complementary proteomic approaches to maximize the identification of proteins related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…However, it is noteworthy that the pH values of all three breeds fell within the normal range defined by the standard for chicken semen [12]. Chicken semen is typically slightly alkaline, with pH values ranging from 6.0 to 8.0 [17,18].…”
Section: Discussionmentioning
confidence: 80%
“…However, it is noteworthy that the pH values of all three breeds fell within the normal range defined by the standard for chicken semen [12]. Chicken semen is typically slightly alkaline, with pH values ranging from 6.0 to 8.0 [17,18].…”
Section: Discussionmentioning
confidence: 80%
“…However, it is not linked to sperm functional parameters. To further investigate the influences of glycerol removal methods, additional molecular and biochemical analysis, such as proteomic approaches and oxidative damage ( Soler et al, 2016 ; Rui et al, 2017 ; Vitorino Carvalho et al, 2021 ), would be helpful to identify molecular pathways impacted by the different post-thawing treatments, and for future improvements.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, several sperm and seminal plasma proteins have been identified as potential markers of sperm freezability in the boar, bull, stallion and men [72,73]. The study of the proteomic profile in the sperm of meat-type chickens revealed 50 proteins linked to sperm fertility that are involved in several molecular pathways other than motility, including mitochondria function, sperm maturation, storage within the female reproductive tract and oocyte-sperm interaction [74]. Further studies to better understand sperm biology and fertilization at the molecular level are required to identify novel biomarkers of chicken male fertility to implement cryopreservation technology and improve the long-term in vitro conservation of avian genetic resources.…”
Section: Discussionmentioning
confidence: 99%